The Principles of Application of Machine Learning in Classification of Network Traffic - Antonyuk, Ya.M.; Oleksyuk, T.N.; Kovalenko, Ya.O.; Shiyak, B.A. (Управляющие системы и машины, 2018)
Approaches to classification of network computing traffic on the basis of division of DPI and methods of structural analysis are systematized. The illustration of one of methods of structural analysis is developed. The algorithm which is possible for implementing in vitro is given. Perspectives of use of the given systematization are planned.